2018
DOI: 10.1007/s12034-018-1582-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basalt, silica sand and fly ash on the mechanical properties of quaternary polymer concretes

Abstract: The aim of this study is to manufacture quaternary polymer concretes (PCs) and optimize the weight percentages of the epoxy resin, ultrafine fly ash, silica sand and basalt aggregates. For this, we first manufactured binary PCs of epoxy/basalt, epoxy/silica sand and epoxy/fly ash and then studied the mechanical properties such as compressive, flexural and splitting tensile strength. The mixture design method was used as an approach for design of experiment to reduce the number of tests and optimize the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The criteria for selecting the input variables of this research are the high importance of the weight content of materials, as well as the dimensions of the fillers, which play a crucial role in the mechanical properties of PCs. [44][45][46][47][48] Furthermore, the dimension of the initial crack, which is a parameter affecting the results of fracture mechanics, has also been investigated. 34 Due to the different types of materials used in the structure of PCs, the database is constructed independently of the type of materials.…”
Section: Database Preparationmentioning
confidence: 99%
“…The criteria for selecting the input variables of this research are the high importance of the weight content of materials, as well as the dimensions of the fillers, which play a crucial role in the mechanical properties of PCs. [44][45][46][47][48] Furthermore, the dimension of the initial crack, which is a parameter affecting the results of fracture mechanics, has also been investigated. 34 Due to the different types of materials used in the structure of PCs, the database is constructed independently of the type of materials.…”
Section: Database Preparationmentioning
confidence: 99%
“…The centrally cracked Brazilian disk (CBD) specimen, due to the simple geometry, ease of fabrication, easy test setup, and ability to be tested with conventional test equipment and fixtures, 1 is frequently used for determining the stress intensity factor (SIF) of brittle materials such as rocks, 2,3 glasses, 4 ceramics, 5 and polymer concretes. [6][7][8][9][10][11] The CBD specimen can be applied to evaluate the SIF and T-stress of pure mode I, pure mode II, and mixed mode I/II. The SIF indicates the intensity of stress singularity around the crack tip.…”
Section: Introductionmentioning
confidence: 99%
“…After research, the results of their study showed that composite tiles made with 70% HDPE performed and were of higher quality. Several experimental investigations into the usage of recycled PET bottles as a substitute for natural aggregates in concrete as well as resin in polymer concrete have recently been released [19]. Akinwumi [20] demonstrated the development of stabilized soil blocks from shredded plastic waste, concluding that 1% finely shredded PET waste (size 6.3 microns) by weight could be used for active block stabilization.…”
Section: Introductionmentioning
confidence: 99%